2012
DOI: 10.1111/ejh.12005
|View full text |Cite
|
Sign up to set email alerts
|

High serum vascular endothelial growth factor level is an adverse prognostic factor for high‐risk diffuse large B‐cell lymphoma patients treated with dose‐dense chemoimmunotherapy

Abstract: Pretreatment s-VEGF level is a predictor of PFS after chemoimmunotherapy and may help to further stratify high-risk DLBCL patients into low- and high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…Our results, as well as those of others [31,35], showed that high serum VEGF levels were associated with advanced Ann Arbor stage, high IPI and the presence of B symptoms, which all somehow represent a measure of tumor burden. These results are in concordance with data showing that VEGF signaling is coupled to growth of lymphoma tissue [36].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results, as well as those of others [31,35], showed that high serum VEGF levels were associated with advanced Ann Arbor stage, high IPI and the presence of B symptoms, which all somehow represent a measure of tumor burden. These results are in concordance with data showing that VEGF signaling is coupled to growth of lymphoma tissue [36].…”
Section: Discussionsupporting
confidence: 88%
“…Several study groups have found that elevated serum VEGF is associated with an unfavorable outcome and a poor prognosis in DLBCL, but all of these studies were performed before the rituximab era [13,15,16]. Recently, Riihijärvi et al [35] demonstrated that a high serum VEGF level is an adverse prognostic factor for patients with high-risk DLBCL treated with dose-dense chemoimmunotherapy. They confirmed the impact of serum VEGF levels on progression-free survival in different IPI subgroups and especially in patients with the nongerminal center subtype of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased VEGF activity has been associated with early recurrence in patients with cancer including GBM [10-12]. VEGF can be measured in biofluids such as urine, serum or plasma [13-15].…”
Section: Introductionmentioning
confidence: 99%